BACTERIAL PATHOGENS ASSOCIATED WITH WOUND INFECTIONS AT THE UNIVERSITY OF MAIDUGURI TEACHING HOSPITAL, MAIDUGURI, NIGERIA - GB GADZAMA; SB ZAILANI; D ABUBAKAR; AA BAKARI (Ntec Specialist, 2001)
Background: Wound infection is a significant health problem in many parts of the world especially, Africa. It complicates the recovery of the patient, increases trauma care, prolongs hospital stay and has economic consequences on the patient. It also undermines the cost-effectiveness of wound management objectives in health settings. Objective: The study aims at investigating bacterial pathogens associated with wound infections at the University of Maiduguri Teaching Hospital, Maiduguri, Nigeria. Methods: Each of the 165 various wound specimens included in the study were streaked on blood and MacConkey agar plates, incubated aerobically at 37oC for 24 hours and colonies were identified and characterized using conventional methods. Result: Out of the 165 wound samples cultured and examined bacteriologically, 98.8% were positive for bacterial growth. Pure culture was obtained in 139 (84.2%), mixed growth of two organisms in 24 (14.5%) and 2 (1.2%) were negative for isolate. The most prevalent (57%) of Gram positive organisms was Staphylococcus aureus and of the Gram negative organisms, Proteus spp (16.4%). Twenty (83.3%) out of 24 polymicrobial infections were between Staphylococcus aureus and other organisms and 4(16.7%) were among Gram negative organisms. Conclusion: It is hoped that reports of this type will create greater awareness in the selection of prophylactics and suitable antibiotic therapy for prompt healing of wounds and reduction of emergence of resistant strains.